Persepsi Pemustaka terhadap Program Literasi Multikultural : (Studi Kasus di Perpustakaan Umum Kota Sibolga) - Mutiara Nauli; Elva Rahmah (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This study aims to determine the perceptions of library users towards the multicultural literacy program at the Sibolga City Public Library, as a response to the importance of literacy in building an inclusive society amidst cultural diversity. The method used is descriptive quantitative with a survey technique through a questionnaire to 73 active library users. The research instrument includes 15 statements on the independent variable (multicultural literacy program) based on James A. Banks' theory, and 10 statements on the dependent variable (librarian perception) based on the Ruch and Zimbardo framework. The results of the analysis show that library users' perceptions of the program are in the good category, with an average score of 40.23 out of a maximum of 50, and a standard deviation of 2.89, which indicates the consistency of respondents' responses. For the multicultural literacy program variable, an average score of 60.9 out of a maximum of 75, and a standard deviation of 3.68, is obtained. This indicates that library users feel that this program is very useful in increasing their understanding of cultural diversity. More than 78% of respondents agreed or strongly agreed that the program helped them understand other cultures, think critically about stereotypes, and feel proud of their own cultural identities. Furthermore, 54.79% of respondents expressed their willingness to promote the program to the surrounding community. These findings confirm that the Sibolga City Public Library has successfully fulfilled its role as an inclusive literacy space. The multicultural literacy program not only helps users improve their understanding of culture but also strengthens social cohesion and strengthens intercultural relationships. With this program, the library has functioned as an important agent of social change in creating a more inclusive and tolerant society. It is hoped that this program will continue to develop and be implemented more widely.